Exploring progress with supply chain risk management during the first year of the COVID-19 pandemic - Remko I. van Hoek (Logistics, 2021)
Background: In response to calls for actionable research that considers ongoing pandemic risk dynamics, we explore how risks experienced and risk mitigation techniques used have changed during the first year of the pandemic. Methods: We used a survey and studied six cases; data were collected both at the start of the pandemic and one year into the pandemic. This paper offers the first empirical exploration of the first full year of the pandemic and provides data points from both early and one year into the pandemic. Results: Our findings indicate that not only are pandemic risks far from mitigated, several types of risks have also increased in severity. Multifaceted and multidirectional approaches have been adopted, going well beyond demand and supply risks (the risks most widely considered in the literature) and much more work remains for supply chain managers to mitigate risks and improve supply chain resilience. Conclusions: We find that in addition to the risk management techniques, considering behavioral aspects is key for navigating a pathway towards risk mitigation.
Keywords: 650; change management; COVID-19; risk management